(untitled) (Research, Society and Development, 2026)
The work of the Military Police requires a high capacity for response and physical endurance, due to the unpredictability of occurrences, which are characterized by exposure to risks and the requirement for intense effort. In view of this, the general objective of this study was to analyze the need to implement a guidance program for the practice of physical activities for the operational personnel of the area units of the Military Police of Alagoas. The methodological design was descriptive–exploratory, cross-sectional, with a mixed quantitative–qualitative approach. Data was collected in PMAL Operational Units linked to the Capital Policing Command (CPC). A non-probabilistic convenience sampling strategy was used, with equal distribution per unit, in order to encompass different physical demands of the operational routine. The results indicate that 76% of participants reported having been removed from PMAL operational activities due to service-related illnesses. Regarding physical conditioning, an unsatisfactory scenario was found, as 38% rated their conditioning as fair and 12% as poor, totaling 50% of the sample in these categories. In addition, 94% stated that they had not received institutional guidance on the practice of physical activities within the Corporation. It is concluded that the implementation of an institutional program providing guidance on physical activity practice in PMAL operational units may improve physical conditioning, health, and functional performance of the personnel.